Microneedle‐Based Glucose Biosensors: A Critical Review of Materials, Fabrication Strategies, and Clinical Translation - Gayatri Pathade; Abhijeet Raut; Atul Sherje (Electroanalysis, 2026)
Diabetes mellitus is a common metabolic disease that requires frequent and accurate glucose monitoring to prevent serious complications and improve outcomes of treatment. Traditional glucose‐monitoring methods like finger pricking and injectable insulin delivery are invasive, painful, and often inconvenient for long‐term use which can adversely affect patient compliance. In addition, the poor permeability of the stratum corneum limits the effectiveness of many conventional transdermal systems, highlighting the need for minimally invasive and patient‐friendly alternatives. Microneedle‐based biosensors have attracted considerable interest as promising platforms for continuous glucose monitoring, since they can penetrate the outer layer of skin with minor pain and directly access the interstitial fluid to detect glucose in real time. Microneedle design, materials, fabrication technologies, and sensing strategies have been substantially advanced. However, most of the existing reviews discuss these aspects individually and have limited coverage on the synergistic effects of the microneedle structure, material property, fabrication strategy, and sensing mechanism on the biosensor performance and clinical applicability. This review focuses on the recent advances of microneedle‐based glucose biosensors including different microneedle architectures, fabrication techniques, material systems, and sensing mechanisms such as enzymatic, nonenzymatic, colorimetric, fluorescence‐based, and surface‐enhanced Raman scattering (SERS)–based systems. The effects of microneedle design mechanical properties on sensing efficiency, biocompatibility, and patient comfort are discussed in detail. Current challenges such as biofouling, long‐term stability, manufacturing complexity, and wearable integration are also discussed. Overall, microneedle‐based biosensors are promising for minimally invasive and personalized management of diabetes.